الأعراض المعدية المعوية المتعلقة بضبط سكر الدم عند مرضى الداء السكري - انطانيوس, ميلاد; المرعي, منيف; ميهوب, عصام (Latakia University Journal -Medical Sciences Series, 2019)
إن معظم الدراسات التي تناولت حدوث الأعراض المعدية المعوية عند مرضى الداء السكري, قد اقترحت أن السكري هو السبب في حدوثها, وذلك مقارنة مع أسوياء. وتنوع هذه الأعراض مرتبط بإصابة المرضى بمستويات مختلفة من المرض وبضبط سكر الدم . لذلك قمنا بدراسة التبدل في حالة الأعراض المعدية المعوية تبعا لضبط سكر الدم خلال سنة كاملة عند مرضى سكريين بالاعتماد على الخضاب الغلوكوزي HbA1c كمشعر لتقييم ضبط السكر خلال الأسابيع السابقة للمعايرة . بينت الدراسة أن المرضى الذين لديهم ضبط سيء لسكر الدم ( HbA1c (%9 < يعانون من أعراض معدية معوية بتواتر أعلى مقارنة مع مرضى الضبط الجيد (HbA1c > 9 % ) . كما أظهرت الدراسة أن إعادة ضبط سكر الدم بشكل جيد لدى مرضى الضبط السيء قابله تحسناً واضح في الأعراض المعدية المعوية عند هؤلاء المرضى . Most studies assessing the prevalence of gastrointestinal symptoms in patients with diabetes mellitus have suggested that diabetics are more likely to experience gastrointestinal symptoms compared with non-diabetics. And these symptoms may vary according to the different levels of disease and glycaemic control that the patients experience. Therefore, we have thought of elucidating whether the change in GI symptoms status is associated with glycaemic control during one year depends on glycated Hemoglobin (HbA1c), being an indicator of the levels of glycaemic control through the previous weeks. This study has found that patients with poor glycaemic control (HbA1c >9 %) have a higher prevalence of GI symptoms than those with good glycaemic control (HbA1c <9%). This study has also found that patients with poor glycaemic control have reported an improvement in the gastrointestinal symptoms after good glycaemic control by them.